NMDA receptor antagonists and pain relief: A meta-analysis of experimental trials. (2nd April 2019) - Thompson, Trevor; Whiter, Fiona; Gallop, Katy; Veronese, Nicola; Solmi, Marco; Newton, Paul; Stubbs, Brendon
Abstract : Objective: We conducted a meta-analysis of controlled trials that used experimental models of acute pain and hyperalgesia to examine the analgesic effects of NMDA receptor (NMDAR) antagonists. Methods: Six major databases were systematically searched (to March 2018) for studies using human evoked pain models to compare NMDAR antagonists with no-intervention controls. Pain outcome data were analyzed with random-effects meta-analysis. Results: Searches identified 70 eligible trials (n = 1, 069). Meta-analysis found that low-dose ketamine (<1 mg/kg) produced a decrease in hyperalgesic area (standardized mean difference 0.54, 95% confidence interval [CI] 0.34, 0.74, p < 0.001) and a 1.2-point decrease (95% CI 0.88, 1.44, p < 0.001) in pain ratings from 4.6 to 3.4 on a 0–10 scale (a 26% reduction). Similar analgesia was observed for acute and hyperalgesic models and was constant across the dosing range (0.03–1.00 mg/kg). Moderate to high variability in effect size was observed and mild side effects (e.g., sedation, sensory disturbance) were common. No effects of dextromethorphan were found. Conclusions: Findings provide robust evidence for analgesic and antihyperalgesic effects of ketamine, supporting its utility for acute and chronic pain management. However, pain relief was modest, suggesting ketamine may potentially be most useful when opioids are contraindicated, rapid analgesia is required, or for pain resistant to conventional medication.